Effects of Essential Oils from Cymbopogon spp. and Cinnamomum verum on Biofilm and Virulence Properties of Escherichia coli O157:H7 - Raffaella Scotti; Annarita Stringaro; Laura Nicolini; Miriam Zanellato; Priscilla Boccia; Filippo Maggi; Roberta Gabbianelli (Antibiotics, 2021)
Every year, the pharmaceutical and food industries produce over 1000 tons of essential oils (EOs) exploitable in different fields as the development of eco-friendly and safe antimicrobial inhibitors. In this work we investigated the potential of some EOs, namely Cinnamomum verum, Cymbopogon martini, Cymbopogoncitratus and Cymbopogon flexuosus, on the growth, biofilm formation and gene expression in four strains of enterohemorrhagic Escherichia coli O157:H7. All EOs were analyzed by gas chromatography-mass spectrometry (GC-MS). The antimicrobial activity was performed by using dilutions of EOs ranging from 0.001 to 1.2% (v/v). Subinhibitory doses were used for biofilm inhibition assay. The expression profiles were obtained by RT-PCR. E. coli O157:H7 virulence was evaluated in vivo in the nematode Caenorhabditis elegans. All EOs showed minimal inhibitory concentrations (MICs) ranging from 0.0075 to 0.3% (v/v). Cinnamomum verum bark EO had the best activity (MIC of 0.0075% (v/v) in all strains) while the C. verum leaf EO had an intermediate efficacy with MIC of 0.175% (v/v) in almost all strains. The Cymbopogon spp. showed the more variable MICs (ranging from 0.075 to 0.3% (v/v)) depending on the strain used. Transcriptional analysis showed that C. martini EO repressed several genes involved in biofilm formation, virulence, zinc homeostasis and encoding some membrane proteins. All EOs affected zinc homeostasis, reducing ykgM and zinT expression, and reduced the ability of E. coli O157:H7 to infect the nematode C. elegans. In conclusion, we demonstrated that these EOs, affecting E. coli O157:H7 infectivity, have a great potential to be used against infections caused by microorganisms.